2022
DOI: 10.3389/fneur.2022.886751
|View full text |Cite
|
Sign up to set email alerts
|

Motor, epileptic, and developmental phenotypes in genetic disorders affecting G protein coupled receptors-cAMP signaling

Abstract: Over the last years, a constantly increasing number of genetic diseases associated with epilepsy and movement disorders have been recognized. An emerging group of conditions in this field is represented by genetic disorders affecting G-protein-coupled receptors (GPCRs)–cAMP signaling. This group of postsynaptic disorders includes genes encoding for proteins highly expressed in the central nervous system and involved in GPCR signal transduction and cAMP production (e.g., GNAO1, GNB1, ADCY5, GNAL, PDE2A, PDE10A,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Therefore, the experimental verification of the relationship between GNAL expression and immune cell expression, chemotherapy response, or immunotherapy response in gliomas is imperative. Although the analysis of pathway enrichment revealed that GNAL was associated with several immune-related pathways, there may be other pathways in which GNAL plays an important role, such as the closely related cAMP signaling pathway [ 64 ]. Studies have demonstrated that the cAMP, which acts as a second signaling molecule, can inhibit the progression of glioma [ 65 ], and decreased expression of GNAL may be the main reason for the dysregulation of this pathway in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the experimental verification of the relationship between GNAL expression and immune cell expression, chemotherapy response, or immunotherapy response in gliomas is imperative. Although the analysis of pathway enrichment revealed that GNAL was associated with several immune-related pathways, there may be other pathways in which GNAL plays an important role, such as the closely related cAMP signaling pathway [ 64 ]. Studies have demonstrated that the cAMP, which acts as a second signaling molecule, can inhibit the progression of glioma [ 65 ], and decreased expression of GNAL may be the main reason for the dysregulation of this pathway in glioma.…”
Section: Discussionmentioning
confidence: 99%
“…GNB1 encephalopathy (GNB1-E) is a rare genetic disease caused by pathogenic variants in the G Protein Subunit Beta 1 (GNB1) gene. Only around 68 cases of this disease have been reported to this day worldwide [1][2][3][4]. Characterizing symptoms for GNB1-E are developmental delay, intellectual disability, and various neurological symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…8,14 However, growing evidence suggests the severity of the disease lies on a spectrum with intermediate clinical phenotypes. 15 Although a few studies have examined genotypephenotype correlation in GNAO1-related disorders, [16][17][18] natural history data or severity scores have not been developed, nor have prognostic factors been identified. Defining subgroups of patients with GNAO1-related disorders by severity is a prerequisite for designing more precise natural history studies to identify domains and windows for potential therapeutic interventions, and to plan clinical trials.…”
mentioning
confidence: 99%
“…Recent progress in this area suggests that GNAO1-associated variants perturb Gαo function by different mechanisms, including loss-offunction, dominant-negative, and debatable gainof-function effects, which ultimately lead to GNAO1related disorders. 11,15,18,20,[23][24][25][26] Yet, our understanding of the molecular pathology of GNAO1 and its relationship with the disease symptomatology is far from complete, and many disease-causing variants remain to be characterized.…”
mentioning
confidence: 99%
See 1 more Smart Citation